The time window for the reversal of depigmentation from aggravation to recovery in a non-small-cell lung cancer patient with pre-existing vitiligo using anti-programmed cell death-1 therapy: A case report - Gao, Zhiru; Xu, Yinghui; Zu, Jianjiao; Wang, Xu; Sun, Chao; Qiu, Shi; Guo, Ye; Ma, Kewei (Frontiers in Immunology, 2022)
Immune checkpoint inhibitors have made remarkable breakthroughs in the treatment of lung cancer, bringing significant survival benefits to the patients. A number of adverse events aggravated by immunotherapy in patients with pre-existing autoimmune diseases have been reported in the past, especially skin toxicity, such as rash, pruritus, erythema, and vitiligo. However, whether the exacerbated autoimmune disease is reversible and when it will return to its original state after immunotherapy discontinuation is still inconclusive. In our report, we described a patient diagnosed with non-small cell lung cancer whose vitiligo was stable for about 10 years. We followed up and observed the patient's skin depigmentation for the complete time window, from aggravation of application anti-programmed cell death-1 receptor antibody (anti-PD-1 antibody) to recovery after the withdrawal. We presented the objective images at particular time points using reflectance confocal microscopy and wood’s light. We found that the use of anti-PD-1 antibody aggravated in skin toxicity, but it was reversible, the time window from the beginning to recovery status was approximately 9 months. We used this real case scenario to explain the relationships between immunotherapy and autoimmune diseases.